Reúso de águas cinzas: uma proposta de sistema hidráulico em residências do município de Angicos/RN - Melo, Hayanne Ywricka de Araújo (Universidade Federal Rural do Semi-Árido, 2019)
Recent studies have highlighted the urgent need for actions aimed at the conservation, preservation and reuse of water resources, fundamental for the preservation of life. The reuse of water has taken a prominent place in governmental and academic spheres, especially in regions that present water crisis scenarios similar to those faced by many municipalities in Northeastern Brazil, suchasinthemunicipalityofAngicos/RN.Theobjectiveofthisworkis to present an alternative of more optimized use of water in typical houses to the municipality of Angicos / RN capable of minimizing theeffectsofthewater shortage faced by the region during the last years. It will be shown that the implementation of a secondary hydraulic project, with the implementation of greywater reuse, is feasible both economically and environmentally, contributing directly and indirectly to the renewal of water sources.
Artigo Acadêmico
Keywords: Projeto hidraúlico; Águas cinzas; Angicos; Hydraulic project; Greywater; Angicos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA